Students' competence in making language skill assessment rubric - Memet Sudaryanto; Habib Safillah Akbariski (REID (Research and Evaluation in Education), 2021)
This study aims to describe (1) the need for an assessment of language skills rubrics; (2) students' abilities in creating holistic and analytic rubrics; (3) the potential and relevance of the application of the rubric in the micro-teaching class; (4) the obstacles faced by students in compiling the rubric. This research used mix method to answer the research questions and a quantitative approach to measure students' understanding of the rubric. Basic competence was assessed using the rubric and mapped students' competencies in designing the rubric. The qualitative rubric was used to describe students' difficulties in applying the rubrics produced in the learning process at school. The population of this study was 250 students of Indonesian Language Education in Central Java selected using a random sampling technique. The study shows that (1) students' knowledge of the components presented in the language skill assessment rubric is still low: most students know that the assessment rubric can be done analytically and holistically, but they cannot explain the differences and how to design the language skill assessment rubric. (2) The rubric produced by students in assessing reading and writing skills is good enough and relevant to be applied in the school: 76% for reading skills and 83% for writing skills. (3) The rubric produced in assessing speaking and writing skills is less optimal and not relevant enough: 78% of students are unable to make good rubrics for listening skills, and 49% are unable to make a rubric for speaking skills.